GLUCOSE-FRUCTOSE INDEX IN THE GRAPES - N. V. Gnilomedova; N. S. Anikina; D. Y. Pogorelov (Овощи России, 2016)
Results summarize literature and experimental data on the content of glucose and fructose of different varieties in grapes belonging to different botanical species of Vitis. The ratio of glucose and fructose indicator can be used for fermentation control and prevention of under fermentation in the production of dry wines, as well as an identification parameter to assess the authenticity of grape juice and concentratedmust. The object of the study were grapes of red and white winemaking European and autochthonous varieties, belonging to Vitis, as well as varieties of new selection (Aligote, Albilio, Verdelho, Sersial, Rkatsiteli, White Muscat, Cabernet-Sauvignon, Bastardo of Magarach, Kephesiya, Ekim kara, Golubok). Sugar content in grape samples was inthe range of 180-260 g/l. Total hexoses were determined by HPLC method according to a modified methodology developed by the Department of Chemistry and Biochemistry of Wine of "FSBSI "Magarach ". It was established that the value range of the glucose-fructose index in the grapes cultivated in different viniviticultural regions of the world makes 0.74-1.19. It has been revealed that the glucose-fructose index decreases with the ripening of berries. Low index values are characteristic for the grape that ripens at high temperatures and was cultivated in regions with hot climate. High index valuesare characteristic of table grapes and winemaking grape varieties of the species Vitis labrusca, Vitis amurensis and interspecific hybrids. Within the botanical species we canidentify varieties that tend to accumulate higher volumes of either glucose or fructose. These patterns are equally characteristic of white and red grape varieties. The analytical analyzes of the Crimean winemaking grape varieties resulted in the establishment of the glucose-fructose index for the first time, varying within the range of 0.9-1.06.